2012
DOI: 10.1553/eco.mont-4-2s5
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation changes in an abandoned montane grassland, compared to changes in a habitat with low-intensity sheep grazing – a case study in Styria, Austria

Abstract: In protected areas maintaining existing phytodiversity is an important conservation target. In this study we analysed the effects of abandonment on plant species composition and species richness over a period of nine years in a montane grassland in the Long-term Ecosystem Research (LTER) region Eisenwurzen (Styria, Austria). Additional investigations concerned the number of Red Data List species, plant strategy types, Ellenberg indicator values, indicator values for mowing, grazing and trampling tolerance, tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Vegetation changes due to abandonment Abandonment caused a marked decrease in species richness, Shannon-Index and evenness on all study sites, illustrating the importance of regular mowing for the maintenance of high plant species richness in seminatural grasslands (Ryser et al 1995;Bohner et al 2012). Our findings also suggested that the similarity in plant species composition between abandoned and adjacent managed grasslands decrease with increasing successional age.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Vegetation changes due to abandonment Abandonment caused a marked decrease in species richness, Shannon-Index and evenness on all study sites, illustrating the importance of regular mowing for the maintenance of high plant species richness in seminatural grasslands (Ryser et al 1995;Bohner et al 2012). Our findings also suggested that the similarity in plant species composition between abandoned and adjacent managed grasslands decrease with increasing successional age.…”
Section: Discussionsupporting
confidence: 59%
“…Based on results from this study and in accordance with Table 6 Basic soil physical and chemical properties of the studied managed and abandoned grasslands. Mean values from two sampling dates in June and August 2015 other studies (Bohner et al 2012;Prévosto et al 2011), the following plant attributes appear to be important in grassland succession: tall stature, leaves evenly distributed along the erect stem (erosulate plants), broad leaves, competitive strategy, perennial life cycle, below-ground reserve organs (geophytes), vegetative propagation via rhizomes (rhizomatous species), scrambling life form (leaf tendrils), tolerance to low light availability at different stages.…”
Section: Discussionmentioning
confidence: 94%
“…Mountain meadows were maintained for centuries by local farmers (Tappeiner and Cernusca 1993). Due to socioeconomic factors, a cessation of grassland management is taking place, especially on grassland with marginal agricultural value (Bohner et al 2012;Hinojosa et al 2016) such as extensively managed meadows in mountain regions. Changes in agriculture either by intensification or abandonment have resulted in a reduction of semi-natural grasslands in Europe (Baur et al 2006a;Graf et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, range shifts of species and migrations were reported by several revisitation studies from high altitudes in the Alps (Walther et al 2005;Pauli et al , 2012Erschbamer et al 2006Erschbamer et al , 2009Erschbamer et al , 2011Holzinger et al 2008;Gottfried et al 2012). Long-term observations are also necessary to record changes due to grazing cessation (Bohner et al 2012). It is well known that grazing cessation causes major alterations in vegetation structure, species composition and richness in the lowlands and in the montane zone (Altesor et al 2005;Pavlu et al 2007;Isselstein et al 2007;Bohner et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term observations are also necessary to record changes due to grazing cessation (Bohner et al 2012). It is well known that grazing cessation causes major alterations in vegetation structure, species composition and richness in the lowlands and in the montane zone (Altesor et al 2005;Pavlu et al 2007;Isselstein et al 2007;Bohner et al 2012). An increasing number of research projects also analysed grazing effects at higher altitudes (Schneiter 1997;Camenisch & Schütz 2000;Scheurer 2000;Kala et al 2002;Binkley et al 2003;Dullinger et al 2003;Buttolph & Coppock 2004;Jewell et al 2007;Miller et al 2010;Deléglise et al 2011).…”
Section: Introductionmentioning
confidence: 99%